Application of the Tri-N-Based PBL Learning Model (Niteni, Nirokke, Nambahi) in Class V Elementary School Social Studies Learning - Sutanto Sutanto; Salma Nur Arrifa; Heri Maria Zulfiati (JURNAL PENDIDIKAN IPS, 2023)
This research is motivated by observational data which shows social studies learning by using a learning model that is not in accordance with the circumstances. To respond to this, researchers conducted descriptive qualitative research which aims to implement learning models that are appropriate to the students' circumstances. Researchers observed the activities of teachers and students during learning activities by implementing problem based learning learning models. The Tri-N (Niteni, Nirokke, Nambahi) problem-based learning model is carried out to find out its application in the classroom. The benefit of this research is that students can carry out structured and planned learning activities. This research was conducted for fifth grade elementary school students with a total of 15 students. This study measures all domains related to the learning process. The learning process by implementing Tri-N Niteni, Nirokke, Nambahi-based problem based learning in social studies learning has several stages, namely determining basic questions, compiling project plans, compiling schedules, monitoring students and project progress, assessing results, and evaluating experiences. The results of this study indicate that the application of the Tri-N-based problem based learning model (Niteni, Nirokke, Nambahi) was successfully carried out with all aspects of student achievement achieved.